Examining the effects of tobacco treatment policies on smoking rates and smoking related deaths using the SimSmoke computer simulation model. Issue 1 (1st March 2002) - Levy, D T; Friend, K
Abstract : Objectives: To develop a simulation model to predict the effects of different smoking treatment policies on quit rates, smoking rates, and smoking attributable deaths. Methods: We first develop a decision theoretic model of quitting behaviour, which incorporates the decision to quit and the choice of treatment. A model of policies to cover the costs of different combinations of treatments and to require health care provider intervention is then incorporated into the quit model. The policy model allows for the smoker to substitute between treatments and for policies to reduce treatment effectiveness. The SimSmoke computer simulation model is then used to examine policy effects on smoking rates and smoking attributable deaths. Results: The model of quit behaviour predicts a population quit rate of 4.3% in 1993, which subsequently falls and then increases in recent years to 4.5%. The policy model suggests a 25% increase in quit rates from a policy that mandates brief interventions and the coverage of all proven treatments. Smaller effects are predicted from policies that mandate more restricted coverage of treatments, especially those limited to behavioural treatment. These policies translate into small reductions in the smoking rate at first, but increase to as much as a 5% reduction in smoking rates. They also lead to substantial savings in lives. Conclusions: Tobacco treatment policies, especially those with broad and flexible coverage, have the potential to increase smoking cessation substantially and decrease smoking rates in the short term, with fairly immediate reductions in deaths.